MANAJEMEN PENDIDIKAN ISLAM DALAM PEMBINAAN DISIPLIN SISWA MELALUI KEGIATAN KEAGAMAAN DI SEKOLAH SMKN 5 MAJENE - Mahriah; Muh. Yusuf; Ahmad; Intan Safitri; Kamus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine how Islamic education management is applied in the administration of religious activities and how it impacts the improvement of student discipline at SMKN 5 Majene. Research on this theme in vocational high school settings remains considerably rare compared to studies conducted in pesantren and madrasah environments, making this research an effort to fill that existing gap. To address the research problems, this study employs a descriptive qualitative approach through field research, with data collected via observation, in-depth interviews, and documentation involving 14 purposively selected informants. The data analysis process follows the interactive model proposed by Miles and Huberman, while data validity is ensured through several procedures, namely source triangulation, technique triangulation, member checking, and enhanced observational persistence. The research findings reveal that various religious activities, including congregational prayer, Quranic recitation, and Islamic holiday commemorations, are managed systematically by referring to four management functions: planning, organizing, actuating, and controlling. The majority of students demonstrate active participation in every activity and experience observable behavioral changes, encompassing improved time discipline, greater compliance with rules, and increased regularity in learning activities. Based on the overall findings, this study concludes that the management of religious activities grounded in Islamic education plays a significant role in shaping students' disciplinary character through a process of religious habituation carried out consistently and in a structured manner.